A CHROOCOCCUM AS INDEX OF K AND P DEFICIENCIES IN MEXICAN SOILS - TAMAYO, M R; SANCHEZ MARROQUIN, AY (Instituto Politécnico Nacional, CD MEXICO, DF, MEX, 1948)
Sixth installment of a comprehensive review of present knowledge of viruses, relations between viruses and their vectors, especially arthropods; latency in vector-hosts; increase within the vector; interactions with vectors; vector-specificity; congenital
CIENC MEX
Keywords: CHROOCOCCUM, INDEX, DEFICIENCIES, MEXICAN, SOILS; MULTIDISCIPLINARIA; PATOLOGIA; BACTERIOLOGIA MEDICA